Convenient synthesis of the enantiomerically pure beta-blocker (S)-betaxolol using hydrolytic kinetic resolution - Joshi, Ramesh A.; Garud, Dinesh R.; Muthukrishnan, Murugan; Joshi, Rohini R.; Gurjar, M. K. (Tetrahedron-Asymmetry, 2005)
Enantiopure (S)-betaxolol was prepared in an extremely simple and practical way using hydrolytic kinetic resolution of a terminal epoxide by Jacobsen's catalyst. High enantiomeric purity (99% ee) has been achieved and the method is amenable to industrial scale-up. (c) 2005 Elsevier Ltd. All rights reserved.

Concise synthesis of beta-blockers (S)-metoprolol and (S)-betaxolol using hydrolytic kinetic resolution - Muthukrishnan, Murugan; Garud, Dinesh R.; Joshi, Rohini R.; Joshi, Ramesh A. (Tetrahedron, 2007)
Enantiopure (S)-metoprolol and (S)-betaxolol were prepared in an extremely simple and practical way using Jacobsen's hydrolytic kinetic resolution of terminal epoxides in isopropanol. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: beta-blockers; betaxolol; Hydrolytic kinetic resolution; metoprolol

Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.

Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.

Continuous flow multipoint dosing approach for selectivity engineering in sulfoxidation - Kulkarni, A. A.; Nivangune, N. T.; Joshi, Rohini R.; Joshi, Ramesh A. (Organic Process Research & Development, 2013)
A continuous synthesis approach with multipoint dosing of one of the reagents is demonstrated for the synthesis of sulfoxide compounds such as proton pump inhibitors. Use of multipoint dosing of the oxidizing agent helped to minimize the possibility of over-oxidation leading to sulfone. Different oxidizing agents were used, and the effect of various parameters (viz. mole ratio of sulfide to oxidizing agent, temperature, residence time, concentration of oxidizing agent, etc.) on the yield of the desired sulfoxide compound was studied. Single-point and multipoint dosing approaches of the oxidizing agent were used for the most promising set of parameters. The performance was compared in terms of conversion of sulfide and the selectivity of the desired sulfoxide. Numbering up approach was used to produce the sulfoxide in a relatively large quantity at laboratory scale with complete conversion and over 99% selectivity for the sulfoxide.